To solve the quadratic equation \(x^2 + 8x = 9\) by completing the square, follow these steps:
-
Move the constant term to the other side of the equation: \[ x^2 + 8x - 9 = 0 \] or, equivalently, \[ x^2 + 8x = 9. \]
-
To complete the square, take the coefficient of \(x\) (which is 8), divide it by 2, and square it: \[ \left(\frac{8}{2}\right)^2 = 4^2 = 16. \]
-
Add and subtract this square (16) on the left side of the equation: \[ x^2 + 8x + 16 - 16 = 9, \] or rewriting this gives: \[ (x + 4)^2 - 16 = 9. \]
-
Now, rearrange the equation: \[ (x + 4)^2 = 9 + 16, \] which simplifies to: \[ (x + 4)^2 = 25. \]
-
Take the square root of both sides: \[ x + 4 = \pm 5. \]
-
Now, solve for \(x\) by isolating it in both cases: \[ x + 4 = 5 \quad \Rightarrow \quad x = 5 - 4 = 1, \] and \[ x + 4 = -5 \quad \Rightarrow \quad x = -5 - 4 = -9. \]
Thus, the two values that solve the quadratic equation \(x^2 + 8x = 9\) are: \[ x = 1 \quad \text{and} \quad x = -9. \]